PEMANFAATAN ALPHA LIPOIC ACID SEBAGAI INHIBITOR DEGENERASI PROTEIN TAU UNTUK PENCEGAHAN CHRONIC TRAUMATIC ENCEPHALOPATHY - Rudy Gunawan,* Nastiti Bekti Utami,* Gusfita Trisna Ayu Putri,* Nadia Jean Romadhon,* Khanif Muflikh (Neurona Majalah Kedokteran Neuro Sains, 2017)
INTRODUCTION CHRONIC TRAUMATIC ENCEPHALOPATHY CTE IS PROGRESSIVE NEURODEGENERATIVE SYNDROME CAUSED BY REPEATED BLUNT OBJECT INJURY AFFECTS THE HEAD THIS CONDITION RESULTS IN DEGENERATION OF TAU A PROTEIN THAT CAN HELP STABILIZE AND SUPPORT CERTAIN STRUCTURES IN BRAINS CELLS INCLUDING INTERNAL TRANSPORT SYSTEM OF THE BRAINS CELL